THE CREATION OF TOURISM EXPERIENCES QUALITY TO INCREASE THE INTENTION OF TOURIST LOYALTY - Taufik HIDAYAH, Riski; HURRIYATI, Ratih; HENDRAYATI, Heny; ADI WIBOWO, Lili; GAFFAR, Vanessa (International Journal of Psychosocial Rehabilitation, 2020)
The competition makes research on tourist loyalty seen as important because all efforts to retain tourists will be far more efficient when compared to businesses and efforts to attract new tourists to visit. This research aims to determine the effect of the experience quality on the intention of Ciletuh-Palabuhanratu Geopark tourist loyalty in West Java. The factors tested in this research are the experience quality and the intention of loyalty. The research method used is verification methods. The population in this research are tourists who have visited the Ciletuh-Palabuhanratu Geopark. The sampling technique used in this research is non-probability sampling with a purposive sampling method with a total sample of 100 respondents. The analytical method used in this research is the analysis of the Spearman rank correlation coefficient and the coefficient of determination at a significant level of 5%.